Targeting Alpha-Synuclein as a Therapy for Parkinson’s Disease - Fields, Carroll Rutherford; Bengoa-Vergniory, Nora; Wade-Martins, Richard (Frontiers in Molecular Neuroscience, 2019)
Parkinson’s disease is one of the most common neurodegenerative disorders with a global burden of approximately 6.1 million patients. Alpha-synuclein has been linked to both the sporadic and familial forms of the disease. Moreover, alpha-synuclein is present in Lewy-bodies, the neuropathological hallmark of Parkinson’s disease, and theis protein and its aggregation have been widely linked to neurotoxic pathways that ultimately lead to neurodegeneration. Such pathways include autophagy/lysosomal dysregulation, synaptic dysfunction, mitochondrial disruption, and endoplasmic reticulum and oxidative stress. Alpha-synuclein has not only been shown to alter cellular pathways, but also to spread between cells, causing aggregation in host cells. Therapeutic approaches will need to address several, if not all, of these angles of alpha-synuclein toxicity. Here we review the current advances in therapeutic efforts for Parkinson’s disease that aim to produce a disease modifying therapy by targeting the spread, production, aggregation, and degradation of alpha-synuclein. These include: receptor blocking strategies whereby putative alpha-synuclein receptors could be blocked inhibiting alpha-synuclein spread, alpha-synuclein reduction which will decrease the amount alpha-synuclein available for aggregation and pathway disruption, the use of small molecules in order to target alpha-synuclein aggregation, immunotherapy and the increase of alpha-synuclein degradation by increasing autophagy/lysosomal flux. The research discussed here may lead to a disease modifying therapy that tackles disease onset and progression in the future.